2015
DOI: 10.5381/jot.2015.14.1.a3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the capabilities of Enterprise Architecture modeling tools for Visual Analysis.

Abstract: In model analysis activities, it is critical to make early statements and diagnosis from a high level of abstraction. Currently, these tasks are difficult to perform, and they require both the involvement of experts and the elaboration of specialized artifacts. Furthermore, the complexity of the tasks increases as models become bigger and more detailed. In other contexts, it has been noticed that total / holistic / unfiltered visualizations may give insight about the models, providing analysts a starting point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Regarding the issue of high effort in using tools, Naranjo et al [50] conducted a study on enterprise architecture modeling tools and how they support visual analysis and understanding of the created models. Pourali and Atlee [51] conducted an empirical study that identified the barriers to adopting modeling tools.…”
Section: Addressing the Challengesmentioning
confidence: 99%
“…Regarding the issue of high effort in using tools, Naranjo et al [50] conducted a study on enterprise architecture modeling tools and how they support visual analysis and understanding of the created models. Pourali and Atlee [51] conducted an empirical study that identified the barriers to adopting modeling tools.…”
Section: Addressing the Challengesmentioning
confidence: 99%